(untitled) (Nepal Journal of Epidemiology, 2012)
It is clear that academic dissemination has a system of checks and balances which authors may experience as barriers. We all want to be sure that scientific information disseminated in academic journals is based on solid data, ethically collected and correctly interpreted. The process of peer reviewing helps to prevent bad science and/or poor scientific papers being published. Many published scientific papers differ from the original submitted manuscript since papers go through a process of peer-review, editing and rewriting. However, there are other potential obstacles in the field of academic publishing. This paper is a case-study of one methods paper which stumbled upon a number of barriers related to the viability and continued existence of a number of academic journals in Nepal. Finally, we offer some advice to help health journals to survive when their editors leave. DOI: http://dx.doi.org/10.3126/nje.v2i4.7093 Nepal Journal of Epidemiology Vol.2(4) 2012 pp.213-215